2023
DOI: 10.1097/aog.0000000000005306
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Perinatal Transmission of Hepatitis C Virus

Mona Prasad,
George R. Saade,
Rebecca G. Clifton
et al.

Abstract: OBJECTIVE: To estimate the rate of perinatal transmission of hepatitis C virus (HCV) infection, to identify risk factors for perinatal transmission of HCV infection, and to determine the viremic threshold for perinatal transmission. METHODS: This was a prospective, multicenter, observational study of pregnant individuals at less than 24 weeks of gestation screened for HCV infection from 2012 to 2018 in the Eunice Kennedy Shriver National Institute of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The parent trial represents the largest cohort of patients with HCV positivity during pregnancy and included prospective collection of detailed information. 14 Use of this data set allowed us to examine multiple factors associated with breastfeeding in detail. However, 25.0% of participants in the original study were excluded due to lack of data on the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parent trial represents the largest cohort of patients with HCV positivity during pregnancy and included prospective collection of detailed information. 14 Use of this data set allowed us to examine multiple factors associated with breastfeeding in detail. However, 25.0% of participants in the original study were excluded due to lack of data on the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary analysis of An Observational Study of Hepatitis C in Pregnancy, a multicenter observational cohort of pregnant people with singleton gestation and HCV seropositivity, conducted by the Eunice Kennedy Shriver National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network. 14 The IRB of The Ohio State University determined that this analysis did not require review due to use of de-identified data only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2000 to 2019, hepatitis C virus (HCV) prevalence among pregnant people in the US increased 10-fold . Recent data demonstrate that HCV is transmitted in 7% to 8% of births to people with HCV . This rise in HCV infections among pregnant people is emerging as a public health concern for women and children …”
Section: Introductionmentioning
confidence: 99%
“…In this month's issue of Obstetrics & Gynecology , Prasad et al 1 (see page 449) report data from the Eunice Kennedy Shriver National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network (MFMU) on the incidence of and risk factors for perinatal transmission of hepatitis C virus (HCV). This was a prospective, multicenter, observational study of pregnant individuals with HCV infection conducted between 2012 and 2018 in 38 participating hospitals (mostly academic) in the United States, whose primary outcome was to determine the rate of and viremic threshold for HCV perinatal transmission.…”
mentioning
confidence: 99%